The Chicken Sisters - Numeroff, Laura Joffe; Collicott, Sharleen (New York : Laura Geringer Book, 1997)
The Chicken sisters drive a troublesome wolf home to his mother with their overwhelming eccentricities.
"Ages 3-7"--Cover p. [4].
Accelerated Reader AR